Pengembangan Media Pembelajaran Interaktif Berbasis Canva untuk Meningkatkan Hasil Belajar Peserta Didik pada Pembelajaran IPA Kelas VI SD Negeri Gumilir 05 - Nur Alfi Fatmawati; Subuh Anggoro (UM Purwokerto Press, 2025)
The development of interactive learning media is a factor that can influence student learning outcomes. This research aims to analyze the effect of developing interactive learning media on student learning outcomes. This research is a Research and Development (RnD) type study aimed at developing and producing a product. The development of this research refers to the 4-D model (Define, Design, Development, and Dissemination) developed by Thiagarajan, which was conducted at SD Negeri Gumilir 05, North Cilacap District, Cilacap Regency. The research population consisted of sixth-grade students at SD Negeri Gumilir 05, with a research sample of 6 students (3 students from class VI A and 3 students from class VI B). Class VI A with 23 students served as the experimental class, while class VI B with 25 students served as the control class. Data collection techniques included observation, documentation, and questionnaires. Prerequisite tests were conducted before hypothesis testing, consisting of normality tests, homogeneity tests, and independent T-tests. The research results obtained from the t-test and simple linear regression analysis showed that the development of Canva-based interactive learning media had a 5% effect on the science learning outcomes of Class VI students at SD Negeri Gumilir 05.